Beyond A “Failed” State: The Role Of Local Politics And The Informal Economy In Post-1991 Somalia. - Chen, Jau-Yon (Advances in Social Sciences Research Journal, 2019)
Contrary to the stereotypical notion that a "failed" state also results in complete economic collapse, Somalia is a classic example of a vibrant economy without any functioning government institutions. For the Somali people, the informal economy has emerged not only as a daily survival mechanism; it also represents their resiliency and determination to make the best out of the worst situations. In addition to serving as Somalia's socioeconomic lifeblood, informal economic activities like livestock trade and petty commerce have kept this country linked with the global economy despite its international political isolation. This paper highlights two important themes. The first is how the informal economy in Somalia and in many war-torn nations has served as an effective grassroots response to non-existent governing systems. The second is how the localization of politics based on religious principles and traditional legal structures have played a vital role in maintaining communal peace and social order.